Immune cell contribution to vascular complications in diabetes - Ma, Lingli; Zhang, Xuejiao; Li, Zimeng; Wang, Qing (Frontiers in Endocrinology, 2025)
Diabetes mellitus often results in vascular complications, significantly impacting patients’ well-being. This review focuses on the role of immune cells in these complications, examining their mechanisms, biomarkers, and treatment strategies. Immune cells, including macrophages, T cells, and B cells, contribute to the development of both macrovascular and microvascular complications by secreting inflammatory factors and modulating immune responses. For instance, in diabetic coronary artery disease, macrophages form foam cells and promote inflammation, whereas in diabetic nephropathy, an imbalance in T-cell subsets exacerbates the condition. Novel immune-related biomarkers, such as soluble cytokine receptors and specific microRNAs, offer new avenues for early diagnosis and monitoring. Current treatments focus on inflammation and oxidative stress, while emerging therapies, including stem cell treatment and precision medicine, show promise but also present challenges. This review systematically summarizes and analyzes pertinent research. Its significance lies in synthesizing current research findings, identifying knowledge gaps, and providing guidance for future basic research and clinical practice. By elucidating the critical role of immune cells in diabetic vascular complications, it aids in the development of new therapeutic targets and more effective treatment strategies. Moreover, the exploration of novel biomarkers opens up the possibility of early disease intervention, and the review of the current treatment landscape and challenges encourages clinicians to make more rational treatment decisions. Overall, the aim is to enhance patients’ prognoses, alleviate the medical burden, and advance progress in diabetes treatment.